Natural Helicobacter infection modulates mouse intestinal muscularis macrophage responses - Hoffman, Sara M.; Fleming, Sherry D. (My University, 2013)
Helicobacter species are common laboratory pathogens which induce intestinal inflammation and disease in susceptible mice. Since in vitro studies indicate that Helicobacter products activate macrophages, we hypothesized that in vivo Helicobacter infection regulates the inflammatory response of intestinal muscularis macrophages from C57Bl/6 mice. Helicobacter hepaticus infection increased surface expression of macrophage markers F4/80, CD11b, and MHC-II within whole intestinal muscle mounts. However, constitutive cytokine and chemokine production by macrophages isolated from infected mice significantly decreased compared to macrophages from uninfected mice despite no detectable bacterial products in the cultures. In addition, muscularis macrophages from infected mice up-regulated FIZZ-1 and SK-1 gene expression, suggesting the macrophages had an anti-inflammatory phenotype. Corresponding with increased anti-inflammatory gene expression, macrophages from infected mice were more phagocytic but did not produce cytokines after stimulation with LPS and IFN-γ or immune complexes and IL-4. Therefore, the presence of Helicobacter infection matures intestinal muscularis macrophages, modulating the constitutive macrophage response to become more antiinflammatory and resistant to secondary stimulation.
Keywords: Helicobacter; Macrophage; Intestine; Inflammation; Infection